ANALISIS STRATEGI PEMBELAJARAN GURU TERHADAP SISWA LAMBAN BELAJAR - Fitria Causari; Rauzah; Martines; Agus Kistian; Muammar F (LPPM Universitas Cipta Mandiri, 2026)
This study aims to describe teachers’ strategies in teaching slow learner students in Grades I and VI at SDN 1 Pagar Air. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews with Grade I and Grade VI teachers at SDN 1 Pagar Air. The results showed that the learning strategies implemented by teachers in teaching slow learner students include: (1) classroom management by placing slow learner students in front-row seating positions or using a U-shaped seating arrangement; (2) the use of varied teaching methods adjusted to students’ characteristics and needs; (3) providing motivation to slow learner students to enhance their enthusiasm and self-confidence in learning; and (4) conducting learning evaluations adjusted to the abilities of slow learner students.